Àrẹ Lekan Àrẹ: A Tribute to a Warrior for all Battles - Toyin Falola (Yoruba Studies Review)
In the forest of songs yours is a fertile lyric weaved for every ear. In the sky of words your lines are rainbow, brighter than the moon, illuminating beyond the stars. Àrẹ, now that the flute of death blew beyond the seven hills of Ìbàdan, I o ̀ fer an elegy to the man whose impacts shaped our lives, a man whose anvil forged the future we desired. Àjanà ̀ku, the ́ elephant that rumbles the forest. If death would have loved to receive money, we would have offered him money. If death would have loved to be offered a thousand rams, we would have loved to slaughter them. But death took you, beyond the earth where the feet of children learn to walk without stumbling. You—father, mentor. You—Achiever. Catalyst.